Prognosis in stage II colon cancer: Expanding the horizons of risk factors - Novoa Díaz, María Belén (2025)
In the following editorial, we discuss the article by Wu et al. In this contribution, we critically review the authors’ perspective and analyze the relevance of the results obtained in the original article of clinical research by Liu et al. We consider that additional factors associated with colon cancer progression have recently been described in extensive clinical research, and should be included in this analysis to achieve a more accurate prognosis. These factors include inflammation, gut microbiota composition, immune status and nutritional balance, as they influence the post-surgical survival profile of patients with stage II colorectal cancer. We also address the clinical implementation and limitations of these analyses. Evaluation of the patient´s entire context is essential for selection of the most appropriate therapy.